Understanding the individual values of working and non-working wives in Malaysia - Zawawi, Dahlia; Md Sidin, Samsinar (Universiti Putra Malaysia Press, 2015)
Changes in the socio-cultural environment such as the emergence of dual career for women are seen to be an influence to the values of the specified gender. Malaysian society differs from the West in terms of family composition and structure, values, norms and behaviour, which affect the role of wives. This study is considered preliminary and investigates the values of women, specifically the wives, across various areas in Peninsular Malaysia in an effort to further understand the uniqueness of this group. The methodology entails a survey approach using structured questionnaires on a sample of 1252 wives throughout Malaysia. Quota sampling was used to ensure representativeness of the Malaysian household's social diversity. Findings revealed a few similarities and also differences in terms of values between wives across the various locations and levels of education.